Investigation of the magnetic anisotropy in a series of trigonal bipyramidal Mn(ii) complexes. Issue 41 (8th July 2019) - Hay, Moya A.; Sarkar, Arup; Marriott, Katie E. R.; Wilson, Claire; Rajaraman, Gopalan; Murrie, Mark
Abstract : The trigonal symmetry around the Mn II ion is fine-tuned to control the rhombic zero-field splitting. Abstract : Understanding how the magnetic anisotropy in simple coordination complexes can be manipulated is instrumental to the development of single-molecule magnets (SMMs). Clear strategies can then be designed to control both the axial and transverse contributions to the magnetic anisotropy in such compounds, and allow them to reach their full potential. Here we show a strategy for boosting the magnetic anisotropy in a series of trigonal bipyramidal Mn(ii ) complexes – [MnCl3 (HDABCO)(DABCO)] (1 ), [MnCl3 (MDABCO)2 ]·[ClO4 ] (2 ), and [MnCl3 (H2 O)(MDABCO)] (3 ). These have been successfully synthesised using the monodentate [DABCO] and [MDABCO] + ligands. Through static (DC) magnetic measurements and detailed theoretical investigation using ab initio methods, the magnetic anisotropy of each system has been studied. The calculations reveal that the rhombic zero-field splitting (ZFS) term ( E ) can be tuned as the symmetry around the Mn(ii ) ion is changed. Furthermore, an in silico investigation reveals a strategy to increase the axial ZFS parameter ( D ) of trigonal bipyramidal Mn(ii ) by an order of magnitude.